Asuragen Inc. (June 2008) - Labourier, Emmanuel; Winkler, Matthew
Asuragen is a fully integrated molecular diagnostics company with products and services that incorporate cutting-edge technologies for isolating, detecting and quantifying nucleic acids. Asuragen''s Signature ®® product line offers streamlined methods for the detection of important genetic alterations and innovative RNA-based solutions for molecular oncology. The company has also pioneered research on microRNA (miRNA) function, isolation and detection in clinical samples. Asuragen is leveraging its broad intellectual property portfolio to build a significant business focused on miRNA/mRNA molecular diagnostics and pharmacogenomic/clinical laboratory molecular services. A near-term goal is to introduce next-generation miRNA-based diagnostic assays to improve tumor classification, monitor disease progression and potentially allow earlier detection of cancer. Asuragen''s miRNA therapeutics development program has recently been carved off into a new sister company, Mirna Therapeutics (TX, USA).